2019
DOI: 10.1016/j.dib.2019.104629
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of EEG power integral, spontaneous recurrent seizure and behavioral responses following combination drug therapy in soman-exposed rats

Abstract: This article investigated the efficacy of the combination of antiepileptic drug therapy in protecting against soman-induced seizure severity, epileptogenesis and performance deficits. Adult male rats with implanted telemetry transmitters for continuous recording of electroencephalographic (EEG) activity were exposed to soman and treated with atropine sulfate and the oxime HI-6 one minute after soman exposure and with midazolam, ketamine and/or valproic acid 40 min after seizure onset. Rats exposed to soman and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 9 publications
14
38
0
Order By: Relevance
“…Although several animal models of chemically induced SE have shown that the anticonvulsive effectiveness of benzodiazepines significantly decreases with increasing delay in administration, 37 our current findings demonstrate the benefit to MDZ administration even when treatment is delayed in a human-relevant mouse model. Consistent with our previous observations in rats, 7,11,15 the present study demonstrated that in GD-exposed Es1 −/− mice, MDZ treatment delayed to 40 min after seizure onset was unable to significantly reduce seizure activity, or prevent epilepto-genesis or neuronal loss. The current findings are also in agreement with our previous study in male Es1 −/− mice in which MDZ (5 mg/kg) at 15 min after GD-induced seizure onset was unable to prevent SRS or brain pathology.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although several animal models of chemically induced SE have shown that the anticonvulsive effectiveness of benzodiazepines significantly decreases with increasing delay in administration, 37 our current findings demonstrate the benefit to MDZ administration even when treatment is delayed in a human-relevant mouse model. Consistent with our previous observations in rats, 7,11,15 the present study demonstrated that in GD-exposed Es1 −/− mice, MDZ treatment delayed to 40 min after seizure onset was unable to significantly reduce seizure activity, or prevent epilepto-genesis or neuronal loss. The current findings are also in agreement with our previous study in male Es1 −/− mice in which MDZ (5 mg/kg) at 15 min after GD-induced seizure onset was unable to prevent SRS or brain pathology.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with our previous findings in male rats in which MDZ (1-9 mg/kg, IP) at 40 min after GD-induced SE dose-dependently increased survival. 15 Survival data from the present mouse study show that when MDZ treatment is delayed to 40 min after SE onset, a dose of at least 9 mg/kg is needed to obtain a survival percentage (78.6%) that is comparable with the results of survival (66.7%) from a prior study in which 5 mg/kg (IP) of MDZ was administered 15 min after SE in male mice. 20 The current study to include a delay of 40 min for the administration of MDZ after the onset of CWNA-induced seizure is highly relevant to a time point when treatments may be provided by first responders in a mass casualty CWNA attack.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations